(untitled) (Journal of Psychiatrists’ Association of Nepal, 2021)
Introduction: Obesity has significant physical and psychological implications along with severe impacts on social and interpersonal relationships of individuals. The present work is a comparative study between normal weight, overweight and obese individuals with respect to their personality traits and attachment in romantic relationships, it also aims to explore the relationship of body mass index with the variables chosen. Material And Method: The total sample size was 90. The study was conducted upon three groups-the three groups consisted of 30 normal weight participants, 30 overweight participants and 30 obese participants each. Participants were grouped on the basis of their Body Mass Index (BMI)- which was calculated from self-reported measures of height and weight. All participants were administered the NEO-Five Factor Inventory and the Experiences in Close Relationships- Revised Questionnaire. On the basis of the obtained data, an Independent Samples t-test was done to see if there existed any significant difference between the groups. A Pearson’s coefficient correlation was performed for the total sample and a Stepwise multiple regression analysis was performed to see if any of the variables were significant predictors of BMI for the present sample. Results: Significant differences existed between the groups in case of neuroticism, extraversion, openness and conscientiousness. The BMI of adults in the present sample has a significant positive correlation with openness and anxious attachment in romantic relationships and a significant negative correlation with extraversion and conscientiousness. Openness and conscientiousness were also significant predictors of BMI for the present sample. Conclusion: The study adds significant findings to the interaction of obesity with the big five personality traits and sheds light on how attachment in romantic relationships is often affected by the weight stigma.